(untitled) (PANGEEA, 2025)
Alba Iulia is located between three major geomorphological units: Trascău Mountains, Vinţ Mountains and Secaş Plateau. This pooziţie gives specific geomorphological features. This paper presents these characteristics that require a particular city development program, to preserve the landscape and biodiversity.